A novel method for evaluation of capillarity in human skeletal muscles from confocal 3D images - Janáček, Jiří; Cvetko, Erika; Kubínová, Lucie; Travnik, Ludvik; Eržen, Ida (Microvascular research, 2011)
A well developed capillary bed is essential for proper function of skeletal muscles. We present for the first time a triple immunofluorescent method suitable for staining capillaries and muscle fibre outlines in thick sections of human skeletal muscle, applying antibodies against collagen IV (in red) and F8 (in green) as well as Ulex europaeus lectin, visualized in green fluorescence. Further, we present possibilities for quantitative evaluation of the capillary network which implies the length of capillaries per unit volume of muscle tissue (Lcap/Vmuscle) and the length of capillaries supplying individual muscle fibres per unit fibre length (Lcap/Lfib), per surface area (Lcap/Sfib) and per volume (Lcap/Vfib) as well as the course of capillaries in the muscle. The latter can be described by the tortuosity, orientation and mean capillary length. To get reasonable results we met the following requirements: i) high quality thick tissue sections, from which 3D image data were acquired; ii) immunofluorescent methods suitable for confocal microscopy; iii) penetration of the fluorescent dyes throughout the tissue section; iv) proper 3D image analysis methods for performing reliable measurements and v) control over relevant tissue deformations. The developed methodology is illustrated by results obtained from autopsy or biopsy samples of three human muscles, i.e. vastus lateralis, multifidus and masseter muscle that exhibit differences in genetic background, innervation, tasks and functional activity.
Keywords: musculus masseter; konfokální mikroskopie; Microscopy, Confocal; monoklonální protilátky; mikrocévy; senioři; lidé středního věku; Imaging, Three-Dimensional; Humans; dospělí; počítačové zpracování obrazu; Aged; Masseter Muscle; Quadriceps Muscle; Microvessels; Microscopy, Fluorescence; čtyřhlavý sval stehenní; Antibodies, Monoclonal; Plant Lectins; rostlinné lektiny; Middle Aged; kosterní svaly; lidé; Image Processing, Computer-Assisted; Muscle, Skeletal; fluorescenční mikroskopie; barvení a značení; zobrazování trojrozměrné; senioři nad 80 let; Adult; Staining and Labeling; Aged, 80 and over